The Integration of faith and environment: A pragmatic approach - Bhat, Ali Muhammad (Journal of Islam and Science, 2023)
The cutting down of forests and the depletion of natural sources through destructive technology resulted in the warming of the climate and the diminishing of the ozone layer is a matter of great concern for modern man. Many efforts were taken at the international level to overcome the environmental crisis but all in vain. Divinity has the potential to overcome all such crises at all levels. The Muslim community is charged with the religious responsibility of protecting all aspects of the environment and the protection of the earth and its ecosystem is the first and foremost responsibility. Due to human activities, global warming is a serious threat to the world because of the environmental crisis which has a huge impact on not only humans but all creatures across the globe and raised serious challenges for the future. It seems that this problem started when a modern man stopped understanding himself as the vicegerent of God and trustee of the All-Merciful God and stopped understanding nature as a sacred sign and valuable trust from God. Environmental protection is an important aspect of Islam. This paper aims to understand the significance of religious teachings as a driving force for the majority of human beings. Islamic guidelines are worth to be implemented to protect the ecosystem and ecology for a better future. Islamic teachings in this regard not only serve in academia but its spiritual values mold human behaviors and restrict large-scale politico-colonial engagements, to safeguard the environment.